THE EFFECTIVENESS OF USING MICROSOFT POWERPOINT BASED ON VIDEO LEARNING THROUGH A SCIENTIFIC APPROACH IN THE BIOLOGY E-MODULE OF MONERA FOR INCREASING THE ACTIVITY, INTEREST AND LEARNING OUTCOME OF 10th MIA INSAN CENDEKIA JAYAPURA STUDENTS - Puji Utama, M. Wahyu; Rumahorbo, Basa T; Antoh, Alfred (Jurnal Ilmu Pendidikan Indonesia, 2022)
This study wanted to determine the effectiveness of using Microsoft powerpoint based on video learning through a scientific approach in the biology e-module of monera for increasing the activity, interest and learning outcome of 10th MIA Insan Cendekia Jayapura students. Research Methods Research and Development (R&D). The research sample was conducted in class X MIA SMA IT Insan Cendekia Jayapura with a total of 28 students. The results showed that the feasibility of the E-Module Biology Monera material through the use of Microsoft PowerPoint media based on learning videos was feasible to be used as a learning media material with an average validator rating of 87%. The use of Biology E-Modules can also increase students' learning activities in the learning process with an average percentage result of 80% in the high category, and can increase high learning interest in students with an average percentage of 74%. The increase in student learning outcomes also increased with the n-Gain test results obtained an average of 0.73 in the high category.